Students’ Perception of the Use of ChatGPT in English Writing Skills for Grade Ten at Senior High School - Angelica Tessalonica Napitupulu; Bloner Sinurat; Dumaris E Silalahi (JURNAL PENDIDIKAN BAHASA, 2025)
This research aims to explore tenth-grade students’ perceptions of using ChatGPT in supporting English writing skills at SMA Negeri 3 Pematangsiantar. The research applied a descriptive qualitative method based on the Technology Acceptance Model (TAM), focusing on two constructs: Perceived Usefulness (PU) and Perceived Ease of Use (PEOU). The qualitative approach was chosen to deeply understand students’ experiences, meanings, and subjective views regarding ChatGPT in writing, as qualitative research allows for exploration beyond mere numerical data (Miles & Huberman, 1994, cited in Sugiyono, 2017). The sample consisted of 35 students selected through purposive sampling. Data were collected through a questionnaire and analyzed using descriptive statistics. The findings reveal that students’ perceptions were generally positive, with a stronger inclination toward ease of use. For PEOU, there were 322 agree responses in total (from 12 items), indicating that students perceived ChatGPT as simple to operate, accessible, and effective in writing. For PU, there were 314 agree responses, showing that students recognized ChatGPT’s usefulness in enriching vocabulary, improving grammar, and assisting idea generation. While a few students expressed concerns about overreliance, most perceived ChatGPT as a user-friendly and supportive tool for writing. The research suggests that integrating AI-based applications like ChatGPT, guided by TAM theory, can enhance students’ confidence and engagement in English writing instruction.